Effect of Sodium Glucose Co-Transporter-2 Inhibition on the Aldosterone/Renin Ratio in Type 2 Diabetes Mellitus - Griffin, Tomás P; Islam, Md Nahidul; Blake, Liam; Bell, Marcia; Griffin, Matthew D.; O’Shea, Paula M. (Hormone and Metabolic Research, 2019)
The aldosterone to renin ratio (ARR) is recommended for case detection of primary aldosteronism (PA). Several factors including medications can undermine its diagnostic accuracy. The objective was to explore the effect of Sodium Glucose Co-Transporter-2 Inhibition on the ARR in patients with type 2 diabetes mellitus (T2DM) who were prescribed a Sodium Glucose Co-Transporter-2 Inhibitor (SGLT-2i) as part of routine clinical care. The primary outcomes were intra-individual changes in aldosterone, renin and ARR. Participants were recruited at routine diabetes outpatient visits as part of a prospective longitudinal study. Eligible participants were prescribed standard doses of empagliflozin and sampled at baseline (pre-SGLT-2i) and at their next routine outpatient visit (post-SGLT-2i). After a mean of 198 (±87) days on SGLT-2i treatment (n=20), there was a significant reduction in HbA1c, BMI, eGFR and serum triglycerides and a significant increase in serum creatinine and sodium. Compared with baseline, there was a significant increase in median direct renin concentration (mIU/l) [40.3 (6.2–249.5) vs. 70.2 (7.0, 551.0) (p=0.005)] and no significant change in median plasma aldosterone concentration (pmol/l) [296 (101, 685) vs. 273 (101, 794) (p=0.541)] with a significant reduction in median ARR (pmol/mIU) [6.9 (0.6–70.7) vs. 5.3 (0.2–39.3) (p=0.007)]. The proportion of participants with a screen positive ARR decreased from 20% (pre-SGLT-2i) to 5% (post-SGLT-2i) (p=0.248). Although performed in a relatively small cohort of medically complex patients, the study indicates that SGLT-2i therapy has the potential to cause false-negative screening for PA in the setting of T2DM. Future confirmatory studies should include patients with confirmed PA.
Keywords: sodium glucose co-transporter-2; type 2 diabetes mellitus; hyperaldosteronism; aldosterone; renin